WORN JEANS TROUSER: AN UNUSUAL LIGATURE MATERIAL FOR HANGING (Journal of Forensic Medicine & Toxicology, 2012)
In India, hanging is one of the commonest methods of suicide with rope as the commonest ligature material. The victims of hanging uses different ligature materials, all are readily and easily available. But it is very unusual that the victim removes his or her own clothes for making ligature material for hanging. In the present case of suicidal hanging, the victim convert the worn jeans trouser to ligature material by cutting with available razor blade, which was presumed to be the weapon of his suicide. The use of worn jeans trouser as ligature material for hanging in this circumstances is very unusual and not reported previously.
Keywords: Hanging; suicide; Unusual ligature material; Jeans trouser